Effect of dance therapies on motor-cognitive dual-task performance in middle-aged and older adults: a systematic review and meta-analysis. Issue 22 (23rd October 2021) - Murillo-Garcia, Alvaro; Villafaina, Santos; Collado-Mateo, Daniel; Leon-Llamas, Juan Luis; Gusi, Narcis
Abstract: Purpose: To systematically review the effectiveness of dance-based programs to improve motor-cognitive dual-task performance in middle-aged and older adults. Materials and methods: Five scientific databases were selected to identify the articles included in this systematic review. Ninety-one articles were found in the electronic databases. Fourteen articles fulfilled all inclusion and exclusion criteria. The methodological quality of the studies was assessed with a modified version of Downs and Black checklist. PRISMA guidelines were followed in the data extraction process. The overall effect size of the improvements was calculated through a meta-analysis. Results: All the studies had an acceptable methodological quality. Dance-based interventions had a duration of 8–52 weeks, 1–3 sessions per week, with sessions lasting 40–90 min. According to the overall effect size, dance-based interventions significantly improved dual-task performance (−0.48 with a 95% confidence interval from −0.88 to −0.08). Conclusions: Dance-based intervention programs may be effective at improving the performance on motor-cognitive dual-task in middle-aged and older adults. Apart from the effects on the cognitive Time Up and Go test, dance interventions may also improve speed walking with a cognitive task. All these conclusions must be taken with caution due to the heterogeneity and the small number of articles. Future research can be developed to increase the knowledge on these issues. Implications for rehabilitation: Interventions based on dance as part of rehabilitation can improve the performance on TUG under dual-task condition in aging. Interventions based on dance can be effective to improve the development of some tasks of daily life by reducing time in a motor task under dual task condition in aging. Physical therapists, personal trainers and other clinicians can use different types of dance for improving dual-tasking among the adults.